Analisis Validitas Konstruk, Konvergen, dan Diskriminan dari Instrument Well-Being - Purnamasari, Mega Isvandiana (LPPM Press, 2023)
The purpose of this study is to validate the Well-Being (WB) measurement instrument using confirmatory factor analysis. Instrument validation aims to ensure that the items are able to accurately reflect the WB to be measured. The instrument used in this study is an instrument developed by Riff, with a total of 42 questions covering 6 aspects of WB. A quantitative descriptive approach was used in this study, involving 284 PGSD STKIP PGRI Pacitan students as respondents. Instrument validity was evaluated using confirmatory factor analysis. Three types of validity were calculated, namely construct, convergent, and discriminant validity. The results of the analysis show that construct validity is met with an RMSEA value of 0.78 and a GFI of 0.908, by issuing 18 questions because it has a low factor loading. Furthermore, convergent validity shows that two aspects, namely Positive Relations and Environmental Mastery, have an AVE value of less than 0.5. Finally, discriminant validity is met with no indication of multicollinearity in the questions used. From these results it can be concluded that the WB instrument that can be used consists of 24 questions, with each aspect consisting of 4 items.